Effects of COVID-19 protective face-masks and wearing durations onto respiratory-haemodynamic physiology and exhaled breath constituents - Sukul, P.; Bartels, J.; Fuchs, P.; Trefz, P.; Remy, R.; Rührmund, L.; Kamysek, S.; Schubert, J. K.; Miekisch, W. (European Respiratory Journal, 2022)
Background: While assumed to protect against coronavirus transmission, face-masks may have effects on respiratory-haemodynamic parameters. Within this pilot study, we investigated immediate and progressive effects of FFP2 and surgical masks on exhaled breath constituents and physiological attributes in 30 adults at rest.